A new variety of Trapa incisa (Lythraceae) from Lake Tai, China - Sun, Li-Yong; Jiang, Zheng; Ding, Yu-Long; Yin, Zeng-Fang (Phytotaxa, 2019)
Trapa incisa var. pubescens, a new variety of Trapa incisa from Lake Tai in Jiangsu Province, China, is described. This new variety was found in coastal waters of northeastern Lake Tai. It is highly similar to T. incisa var. incisa and T. incisa var. quadricaudata in phenotype, but it can be distinguished by its sparsely pubescent pedicels and longer pink petals.